An experimental and numerical study on the effects of taper angles and overlap length on the failure and stress distribution of adhesively-bonded Single-Lap Joints - Solmaz, Murat Yavuz; Turgut, Aydin (Association for Scientific Research, 2011)
This paper examines the failures and strengths of joints bonded by a Neoxil CE92 N8 adhesive at different overlap lengths and different taper angles. The study was carried out both as experimental and numerical. In the experimental stage, lap-shear tests on Single-Lap Joints (SLJs) with different taper angles and overlap lengths were conducted. The stress analyses in the SLJs were obtained using a linear Finite Element Analysis (FEA) in numerical stage. It is assumed that adhesive and adherend have both geometrical nonlinearity and linear material behaviour. Scrutinising carefully the surfaces of the SLJs, two different failure types, cohesive failures (CF) and special cohesive failures (SCF) were observed. The obtained numerical results were compared with experimental ones. Results indicate that the increasing of both overlap length and taper angle increase the joint strength and, in particular, the highest strength values in all joint geometries are attained by specimens having a taper angle of 15°. © Association for Scientific Research.
Keywords: Adhesive; Finite element stress analysis; Single lap joint; Taper angle